2008
DOI: 10.1007/s11605-008-0505-z
|View full text |Cite
|
Sign up to set email alerts
|

Cachexia Worsens Prognosis in Patients with Resectable Pancreatic Cancer

Abstract: Cachexia has a significant impact on survival and performance status in palliative patients as well as in patients operated for pancreatic cancer. But tumor-related cachexia is not necessarily dependent on tumor size or load and that metastatic dedifferentiation of the tumor might be a critical step in the development of tumor-associated cachexia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
262
2
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(284 citation statements)
references
References 36 publications
10
262
2
10
Order By: Relevance
“…Outcome results in this analysis indicate that the median difference in survival in BRPC and LAPC patients is separated by a mere six months, like other findings in the current literature (35,70,71). Our study specifically included patients with only borderline resectable and locally advanced disease, which correlates with IIA, IIB, and III AJCC stages.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Outcome results in this analysis indicate that the median difference in survival in BRPC and LAPC patients is separated by a mere six months, like other findings in the current literature (35,70,71). Our study specifically included patients with only borderline resectable and locally advanced disease, which correlates with IIA, IIB, and III AJCC stages.…”
Section: Discussionsupporting
confidence: 66%
“…The next best option is to use data from multiple studies using percentile based summative values. The literature currently uses a plethora of cohort-specific values, including using the lowest median, tertile, quartile, quintile, or standard deviation (19)(20)(21)23,24,27,28,(33)(34)(35)(36)(37)(38) in the study cohort. We validated our cohort's cutoff, by performing ROC curve analysis with regards to acute radiotoxicities which correlates to approximately a TPA of 500.…”
Section: Discussionmentioning
confidence: 99%
“…PDAC is also among the deadliest forms of cancer, with a 93% mortality rate in 5 years following diagnosis 33, 34, 35, 36. Current approaches to treating PDAC include cytotoxic chemotherapy, ionizing radiation, and surgical resection 37, 38.…”
Section: Discussionmentioning
confidence: 99%
“…There is a vast array of published studies showing reduced survival in weight-losing cancer patients and in those with cachexia. Studies have consistently demonstrated that the prognosis for cancer patients with weight loss is worse than that for weight-stable patients (33)(34)(35)(36) . Table 1 summarises the available evidence for reduced survival in a variety of cancers which report hazard ratios of death ranging from 1·63 to 4·2 (37,38) .…”
Section: Malnutrition Cancer Cachexia and Survivalmentioning
confidence: 99%